2021
DOI: 10.3389/fpsyg.2021.642954
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Activity Pre-, During and Post-lockdown COVID-19 Restrictions in New Zealand and the Explanatory Role of Daily Hassles

Abstract: Covid-19 lockdown restrictions constitute a population-wide “life-change event” disrupting normal daily routines. It was proposed that as a result of these lockdown restrictions, physical activity levels would likely decline. However, it could also be argued that lifestyle disruption may result in the formation of increased physical activity habits. Using a longitudinal design, the purpose of this study was to investigate changes in physical activity of different intensities, across individuals who differed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
4
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 46 publications
9
47
4
5
Order By: Relevance
“…Moreover, we have established that in the group who had not met WHO’s recommendations before the lockdown, some participants significantly increased their PA. As found by Hargreaves et al [ 75 ] in their study in New Zealand, vigorous and moderate intensity PA were significantly lower post-lockdown compared to pre-lockdown in those individuals who had been highly active pre-lockdown with simultaneous contrast for moderately active individuals’ pre-lockdown, and vigorous and moderate intensity PA was significantly higher during-lockdown compared to pre-lockdown [ 75 ]. Our PA results show how important it is to analyze the PA data collected during COVID-19 restrictions depending on how active the adolescents were before the restrictions as the pattern of change was different between the groups meeting and not meeting WHO’s recommendations.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, we have established that in the group who had not met WHO’s recommendations before the lockdown, some participants significantly increased their PA. As found by Hargreaves et al [ 75 ] in their study in New Zealand, vigorous and moderate intensity PA were significantly lower post-lockdown compared to pre-lockdown in those individuals who had been highly active pre-lockdown with simultaneous contrast for moderately active individuals’ pre-lockdown, and vigorous and moderate intensity PA was significantly higher during-lockdown compared to pre-lockdown [ 75 ]. Our PA results show how important it is to analyze the PA data collected during COVID-19 restrictions depending on how active the adolescents were before the restrictions as the pattern of change was different between the groups meeting and not meeting WHO’s recommendations.…”
Section: Discussionmentioning
confidence: 76%
“…We can therefore only presume the determinants of this change. According to Hargreaves et al [ 75 ] 35% of participants who increased or maintained their PA levels during lockdown noted that being active “was a good excuse or reason to get outside”. Young people may also want to increase their physical fitness or just have more free time to use it for this purpose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifestyle changes during the state of emergency may affect perceived health status, which negatively affects future health conditions. A previous longitudinal study investigated changes in PA prior to lockdown restrictions being imposed, and across three time periods: pre-, during, and post-lockdown [ 16 ]. The results showed that vigorous and moderate intensity PA were significantly lower during and post-lockdown compared to pre-lockdown in those individuals who had been highly active pre-lockdown [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous longitudinal study investigated changes in PA prior to lockdown restrictions being imposed, and across three time periods: pre-, during, and post-lockdown [ 16 ]. The results showed that vigorous and moderate intensity PA were significantly lower during and post-lockdown compared to pre-lockdown in those individuals who had been highly active pre-lockdown [ 16 ]. More than 40% of community-dwelling Japanese old-old adults perceived a decline their physical fitness during the COVID-19 state of emergency [ 17 ].…”
Section: Introductionmentioning
confidence: 99%